KESIAPAN IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL PADA POLITEKNIK NEGERI PADANG - Sepri Neswardi (Politeknik Negeri Padang, 2018)
In the central government, Reporting and accounting entity will begin implementing full accrual basis accounting in the preparation of government financial statements. The research method is descriptive research with a qualitative approach. This approach is used so that researchers understand how Padang State Polytechnic prepares itself in the application of government accrual accounting standards. Acceleration strategies for applying accrual basis accounting using SWOT matrix analysis. Principally, The Padang State Polytechnic Work Unit is committed to implementing government accounting standards based on the accruals stipulated in PP.71/2010. In terms of commitment, infrastructure and information technology have made several preparations to support the implementation of SAP. The Constraints of implementation PP.71/2010 is that insufficient in understanding PP.71/2010 competencies, so that in the field of accounting or government accounting in general is still lacking, coordination between fellow financial managers and unfair disbursement, socialization and training on SAP accruals, and poor planning. So finally, The strategy of acceleration in the application of SAP accruals at Padang State Polytechnic which is possible to be implemented is an aggressive strategy.